Prevalence of Parasitic Infections in Patients Attending Tertiary Hospital ASCOMS Jammu - Jyoti Kohli; Ajay Puri; Ashok Dhar (Asian Journal of Medical Research, 2020)
Background: Intestinal parasitic infections are endemic worldwide and varies considerably from place to place. According to World health organization two billion people are infected with parasitic infections globally. This prevalence is due to low levels of sanitation, open defecation, lack of safe water supply, poor hygiene, low socio- economic status, age group and impoverished health services.Subjects and Methods:In order to know the infection rate of these intestinal parasites 2500 stool specimens were studied microscopically for parasitic infections by direct wet mount and iodine mount.Results:It was observed that only 5.28% were infected with intestinal parasites. The ova and cysts of various intestinal parasites were identified microscopically and pattern of different isolated parasites were studied and it was observed that most commonly isolated was Giardia intestinalis 69.69%, followed by Entamoebahistolytica 19.69%, Ascarislumbricoides 7.57%, Ankylostomaduodenale 1.51% and Trichuristrichuira 1.51%.Conclusion: The decrease in parasitic infections evidence the success of health education, improved sanitation and healthy lifestyle.